Oral Breakdown of Texturally Complex Gel‐Based Model Food. Issue 3 (2nd September 2015) - Larsen, Danaé S.; Tang, Jingyuan; Ferguson, Lynnette; Morgenstern, Marco P.; James, Bryony J.
Abstract: Until now, the textural complexity of foods and subsequent influence on oral breakdown pathways has not been analyzed. This study evaluated the effect of textural complexity on the oral breakdown of foods by using gel‐based model foods with "built‐in" levels of textural complexity. Twenty subjects chewed and expectorated the model foods at different stages during mastication (chewing cycle). Textural complexity did not significantly impact oral transit time, number of chews or chewing rate. The high complexity (HC) model food followed a significantly different oral breakdown pathway to low complexity and medium complexity samples. During the initial stages of chewing, HC samples broke down into a significantly greater number ( P < 0.05) of significantly smaller particles ( P < 0.05). The surrounding matrices controlled the release of embedded inclusions, ensuring the HC samples followed a dynamic oral breakdown pathway with changes occurring in particle size and number throughout the whole chewing cycle. Practical Applications: The textural complexity of food is associated with a range of differing texture attributes that from the first bite through to the point of swallowing stimulate the senses, creating a variety of texture perceptions. Little is known on how textural complexity can influence oral breakdown pathways. This study has shown how a high complexity model food follows a dynamic oral breakdown pathway where changes in the bolus occur throughout the whole chewing cycle. These results lend themselves to further study on how these constant changes influence perceivable texture and stimulate the senses during eating. It is also hypothesized by the authors that in foods that are more texturally complex, these perceived textures and potential stimulation might positively affect the satiation response.